THE ORIGIN OF SYNAPTONEMAL COMPLEX PROTEINS. SEARCH FOR RELATED PROTEINS IN PROTEOMES OF ALGAE, LOWER FUNGI, MOSSES, AND PROTOZOANS - T. M. Grishaeva; Yu. F. Bogdanov (Вавиловский журнал генетики и селекции)
Proteins similar to known proteins of the synaptonemal complexes (SCs) of seven species of higher eukaryotes, from budding yeast to mouse, which are used as models for studying meiosis, have been sought by bioinformatical methods. In the proteomes of green and brown algae, mosses, a number of lowest fungi, Euglenozoa, Apicomplexa, and some other unicellular eukaryotes, proteins containing the HORMA domain show the greatest similarity to SC proteins of the model organisms. They are close to proteins of lateral SC elements of higher eukaryotes, also bearing the HORMA domain. This domain recognizes the chromatin state and recruits other proteins for SC formation.